Artificial Intelligence for resource recommendation in online education - Georgina Sanabria Medina; Laura Regil-Vargas (Universidad de Guadalajara, 2024)
Artificial Intelligence (AI) has been used in online education for at least a decade, with recent emphasis on teaching-learning processes. The objective of this article is to share the preliminary results of a research on the development of a Recommender System (SR) of educational resources to be applied in an online high school. Under the Design-Based Research methodology, once the algorithm for the SR was developed, it was fed with information from the rubric of an activity and its grade, plus database of resources, made up of images, videos, audios and texts. The results show that SR applied to educational resources favor teaching and learning processes in online education. One of the limitations of the research is that, so far, the SR has only been tested in digital simulators and not in an institutional high school platform. However, with the results of this project, using AI solutions, we can verify contributions to the learning processes in online education. Among the conclusions, multidisciplinary work in AI and education is recognized as a strategy for strengthening learning processes in virtual learning environments.